The youths’ interpretation towards Perpustakaan Raja Tun Uda / Nur Farahanis Salim - Salim, Nur Farahanis (2010)
This study was purposely to investigate the “YOUTHS’ INTERPRETATION TOWARDS PERPUSTAKAAN RAJA TUN UDA” which the library located in Shah Alam. In order to achieve the objectives of the study, sets of questionnaires were distributed to the respondents comprised of youths from 15 years old until 40 years old who visited Perpustakaan Raja Tun Uda. The result of the study could be used to improve the condition, services, collections and facilities in public library in order to attract youths and ensure there would be continuous visit by the youths to ensure the survival of the public library. This study could for further reference and could be improved for future studies.